The nurse practitioner as a bridge to interprofessional research team collaboration in rural community clinics. Issue 5 (1st May 2021) - Ferguson, Laurie Anne; Arnold, Connie; Morris, James; Rademaker, Alfred; Davis, Terry
ABSTRACT: Clinical health outcomes and health disparities can be improved through interprofessional collaborations among multidisciplinary clinicians, health care services researchers, and patients. Bridging gaps between community clinics and urban academic centers allows added valuable perspectives that can lead to improved care and extend clinical research. Nurse practitioners (NPs) who serve as primary care providers in many rural community clinics can facilitate access to clinical trials for patients who are rarely included in health care services research as well as coordinate interprofessional research team collaboration. A NP working in a rural clinic can assist academic-based research teams in designing feasible strategies to address disparities and improve health care of underserved populations. The purpose of this article was to provide an example of a rural provider/urban academic research team collaborating to conduct a health literacy-directed randomized controlled trial to improve colorectal cancer screening in isolated rural community clinics.